Endocrinologic Consequences of Pediatric Posterior Fossa Tumours - (:unkn) unknown (My University, 2015)
0

Intracranial tumors are the second most frequent malignancies in children and posterior fossa is a common location for these neoplasias during childhood. Recent advances in surgical techniques, radiotherapy and chemotherapy resulted in dramatic increase in the survival rates of these children, however they are still source of a significant morbidity and mortality. Endocrinological complications and late sequelae of childhood posterior fossa tumours are common among the survivors of these tumours and include growth retardation, hypothyroidism, pubertal disorders, gonadal dysfunction and osteopenia. These complications have significant impact on the quality of life of the survivors of childhood posterior fossa tumours. In this paper, the frequency, etiology, and management of these complications will be reviewed
Keywords: Endokrinoloji ve Metabolizma; Pediatri